Um estudo sobre a formação continuada do coordenador pedagógico desenvolvida pelo CEFAPRO de Cáceres/MT - Carlos, Rinalda Bezerra (2013)
Continued education of Pedagogical Coordinators of public schools in the region of Cáceres in Mato Grosso takes place in the Center of Education and Updating of Basic Education Professionals (CEFAPRO). Such education has been conceived in the Managers Room Project, which gathers Pedagogical Coordinators (PCs), Principals and Pedagogical Assistants in one site. Among other actions, it determines the strategies for continued education in the schools (Educator s Room Project). Firstly, by attempting to know to which extent PCs are enabled to perform the functions assigned by the Secretary of the State of Mato Grosso (SEDUC/MT), we noticed that the Managers Room Project has not prepared PCs to conduct the continued education in the schools. Thus, we deepened the studies of both continued education in general, regarding the principles proposed by Marcelo (1999) and the multiple dimensions presented by Placco (2006), and the process of professional identity constitution (DUBAR, 2005), in order to analyze how the teachers professional development occurs (CANDAU, 1996, MARCELO, 2009) and, based on Libâneo (2004), Placco and Almeida (2009), consider the attributions assigned to PCs, as well as the difficulties they find in their professional activity (DAVIS; NUNES; ALMEIDA, 2011). This study led us to consider the process of identity constitution related to the PCs professional development and establish the hypothesis that, if the continued education neither prioritizes the process of identity constitution nor values the PCs education needs, therefore, the PCs professional development and, consequently, their performance will be hindered. By considering the study object together with historical-social conditionings, it was possible to evidence that the strategies used by CEFAPRO in Cáceres aim at helping PCs deal with daily school emergencies, rather than educating them in terms of methodological requirements that are inherent to their position; furthermore, they not take into account the PCs values, perceptions, experiences and education needs, causing them to undergo an identity crisis. This paper includes recommendations for an education proposal that considers the importance of research, the students life experience, the knowledge of a range of education strategies, the work systematization, the students adherence, the participation of a multidisciplinary group of educators, as well as the process of identity constitution of the subjects involved in the education course